Endogenous plasticity in neuro-rehabilitation following partial spinal cord lesions - Alstermark, Bror; Pettersson, Lars-Gunnar (Frontiers in Neuroscience, 2014)
Currently, much interest in neuro-rehabilitation is focused on mechanisms related to axonal outgrowth and formation of new circuits although still little is known about the functionality in motor behavior. This is a highly exciting avenue of research and most important to consider when dealing with large lesions. Here, we address endogenous mechanisms with the potential of modifying the function of already existing spinal circuits via associative plasticity. We forward a hypothesis based on experimental findings suggesting that potentiation of synaptic transmission in un-injured pathways can be monitored and adjusted by a Cerebellar loop involving the Reticulospinal, Rubrospinal and Corticospinal tracts and spinal interneurons with projection to motoneurons. This mechanism could be of relevance when lesions are less extensive and the integrity of the neural circuits remain in part. Endogenous plasticity in the spinal cord could be of clinical importance if stimulated in an adequate manner e.g. by using optimal training protocols.